Optimization Of Christian Education Services In The Church In Improving The Creative Economy For The Simalungun Community - Damanik, Rosmalina (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
Optimization of Christian Education services in GKPS is important to improve the right creative economy and can help church residents overcome poverty problems in Simalungung Community. Therefore, church service through Christian Religious Education must prepare people to face change optimally. This research aims to develop the creative economy through Christian Religious Education services at GKPS. The results of this study will offer a paradigm shift in thinking for GKPS congregations, a paradigm of thinking for GKPS ministers, and ministry does not focus on church rites but provides understanding to improve the creative economy through Christian Religious Education service in the church.